Response of Ultra-Narrow Row Cotton to Telone II in Root-Knot and Reniform Infested Fields - Jim Rich; Robert Kinloch; David Wright (EDIS)
This document is ENY-677, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: February 2003.